AFM analysis reveals polymorphism of purified flax rhamnogalacturonans I of distinct functional types. (15th July 2019) - Petrova, Anna A.; Kozlova, Liudmila V.; Gaifullina, Ilzira Z.; Ananchenko, Boris A.; Martinson, Ekaterina A.; Mikshina, Polina V.; Gorshkova, Tatyana A.
Highlights: Structurally and functionally distinct types of flax RGs-I have different shapes. Neither short nor long side chains of flax RGs-I are visualized by AFM as object branching. All types of purified flax RGs-I tend to aggregate. The shape of purified RG-I cannot be deduced yet from the polymer structure. Abstract: Functionally distinct polymers organized on the basis of rhamnogalacturonan I (RG-I) backbone with more than a half of rhamnose residues substituted by the side chains containing mostly galactose were purified from flaxseed mucilage, the primary cell wall of young hypocotyls and tertiary cell walls of bast fibers and characterized by atomic force microscopy. Seed mucilage RG-I with short side chains and unusual O3 substitution showed loose coils or star-like conformations. Primary cell wall RG-I, which included polygalacturonan (PGA) fragments, represented micellar objects and rare long chains. Pure RG-I with long galactan side chains, which was isolated as nascent polysaccharide before its incorporation into the tertiary cell wall of bast fibers was observed as long unbranched objects. RG-I entrapped by cellulose microfibrils in tertiary cell wall was visualized as compact micellar complexes. All types of flax RGs-I tended to aggregate. Relationships between RG-I structure and morphology are discussed.